Ethylene polymerization process
By using a combination of aluminum-containing cocatalyst and antistatic compounds in the ethylene polymerization method, the problems of electrostatic charge and sheeting are solved, and an efficient and low-interference ethylene polymerization process is achieved, ensuring the high quality of the polymer and reactor stable operation.
Patent Information
- Application Number
- CN202380051785.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-21
AI Technical Summary
In ethylene polymerization processes, the occurrence of electrostatic charges may lead to reactor flaking, affecting polymer quality and reactor control, and the use of antistatic agents may inhibit catalyst productivity and affect polymer properties.
Gas phase polymerization is carried out by adding aluminum-containing cocatalysts, aluminum-containing cocatalyst additives and antistatic compounds containing specific structural parts to the catalyst system to reduce the formation of electrostatic charges and the sheeting of the inner wall of the polymerization reactor.
The production of ethylene-based polymers under high productivity and high quality conditions is achieved, preventing the formation of electrostatic charges and flakes, and avoiding negative effects on catalyst productivity and polymer properties.
Smart Images

Figure CN119497724A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a process for the polymerization of ethylene to produce homopolymers and / or copolymers based on ethylene. In particular, the present invention relates to a polymerization process in which the occurrence of electrostatic charges is reduced. Background Art
[0002] In ethylene polymerization processes for producing ethylene homopolymers and / or copolymers, continued research and development efforts spanning several decades have resulted in efficient, large-scale processes that allow the manufacture of high-quality ethylene-based polymers with a wide variety of desired properties under very economical conditions. In such processes, the use of various types of catalysts enables manufacturers to produce such a wide range of attractive products.
[0003] In order to make such a large-scale process run most efficiently, it is of utmost importance that the production process is run with minimal interruptions and under conditions that result in maximum productivity of high-quality products. For example, due to the presence of impurities in the ethylene and other feeds supplied to the polymerization process, static charges may occur in the polymerization reactor, particularly in the gas phase polymerization process, which may cause interference in the process and therefore may cause the reactor to shut down. It should be understood that the occurrence of excessive static charges in gas phase polymerization may lead to reactor sheeting, i.e., the deposition of polymer material on the inner wall of the reactor. In a gas phase reactor, polymer particles are driven by the high superficial velocity of the gas flow and flow turbulently in the reactor. Friction and collision between polymer particles or between polymer particles and the reactor wall can generate static charges on the surface of polymer particles or reactor walls. This phenomenon is well known in the art and is referred to as triboelectric charging or triboelectric charging. When static charges accumulate to be sufficient to overcome the aerodynamic force applied by the gas flow, the charged polymer particles may migrate to the reactor wall and eventually adhere to the wall. Therefore, these particles may cause sheeting on the reactor wall. Such sheeting may cause some polymer particles to be overexposed to polymerization conditions, which may eventually lead to carbonization. When such carbonized particles are present in the polymer product obtained from the reactor, the quality of the polyethylene product is negatively affected. In addition, the presence of sheets may lead to problems with reactor control, which may necessitate shutting down the reactor.
[0004] It will be appreciated that such disruptions and stops will be minimized.
[0005] In ethylene polymerization processes, the use of certain types of catalysts may be more prone to such interferences. For example, metallocene-type catalysts appear to be more sensitive to these types of effects. However, due to their ability to produce ethylene-based polymers with very desirable properties, it is highly desirable to be able to use metallocene-type catalysts in ethylene polymerization processes while suppressing the occurrence of process interferences as much as possible.
[0006] In the art, several methods have been provided in an attempt to mitigate static charge in commercial olefin polymerization reactors. In principle, three approaches are followed to reduce static charge: reactor treatment and modification, which may involve coating the reactor interior with materials that have less tendency to generate static charge; catalyst formulation modification, enabling the catalyst to generate less static charge; and adding antistatic additives directly into the reaction zone. Combinations of these approaches may also be used.
[0007] The approach that is particularly desired is to add an antistatic additive. This approach allows the generation of static charge to be suppressed persistently and controllably. However, antistatic agents are directly added to the catalyst formulation or added to the polymerization process as an additive, typically resulting in the inhibition of catalyst productivity, resulting in the reduction of process economy, or possibly affecting the product properties of the produced polymer, such as it may negatively affect the density or melt index of the polymer. It is believed that some of these effects are derived from the interaction of the active species of the antistatic agent and the catalyst system. Therefore, it is desirable to develop a method for the polymerization of ethylene using an antistatic agent, wherein fully reducing the appearance of static charge formation, without the interference of the polymerization process itself occurring simultaneously.
[0008] This is now provided according to the invention by a process for the preparation of ethylene-based polymers, preferably by gas phase polymerization, wherein the process is carried out by polymerizing a reaction composition comprising ethylene in the presence of a catalyst system, an aluminum-containing cocatalyst, an aluminum-containing cocatalyst adjuvant and an antistatic compound comprising one or more moieties according to formula I:
[0009]
[0010] in:
[0011] ● R1 is H or an aliphatic moiety containing 1 to 4 carbon atoms, preferably H or CH3, more preferably H;
[0012] ● R4 and R5 are moieties containing 1 to 10 carbon atoms, preferably aliphatic or aromatic moieties containing 1 to 10 carbon atoms, more preferably -CH2CH3 or CH3;
[0013] ● R3 and R6 are H or a moiety containing 1 to 10 carbon atoms, preferably an aliphatic or aromatic moiety containing 1 to 10 carbon atoms, more preferably -CH2CH3 or CH3;
[0014] ●R2 is H; a structural part containing 1 to 10 carbon atoms, preferably an amine, aliphatic or aromatic structural part containing 1 to 10 carbon atoms; or R2 forms a linking group to a polymer structure, wherein the compound of formula I forms a functional structural part connected to the polymer chain.
[0015] Such a method allows the production of ethylene-based polymers having desired qualities at desired productivity while preventing the formation of static charges and sheeting on the inner wall of the polymerization reactor.
[0016] Preferably, each of R3, R4, R5 and R6 is a moiety containing 1 to 10 carbon atoms, preferably an aliphatic or aromatic moiety containing 1 to 10 carbon atoms, more preferably -CH2CH3 or CH3. Preferably, R1 is H.
[0017] The moiety of formula I may for example be a 2,2,6,6-tetramethylpiperidine moiety.
[0018] The moiety of formula I may form part of a polymer structure having a polymer repeating unit according to formula II:
[0019]
[0020] in:
[0021] ● R1 is H or an aliphatic moiety containing 1 to 4 carbon atoms, preferably H or CH3, more preferably H;
[0022] ● R7 is an alkyl moiety, preferably an alkyl moiety containing 4 to 10 carbon atoms, more preferably -(CH2) x - a moiety wherein x is 4 to 10, preferably x is 6; and
[0023] ● Each R8 and R9 is H; a moiety comprising 1 to 10 carbon atoms, preferably an aliphatic or aromatic moiety comprising 1 to 10 carbon atoms, more preferably n-butyl, tert-butyl or tert-octyl; 2,2,6,6-tetramethyl-4-piperidinyl; or 4,6-bis(di-n-butylamino)-1,3,5-triazine-2-yl;
[0024] and preferably wherein n≧1 and ≦10.
[0025] In this formula II, R8 may be, for example, H and R9 may be, for example, tert-butyl or tert-octyl; or R8 may be n-butyl and R9 may be 2,2,6,6-tetramethyl-4-piperidinyl.
[0026] Preferably, the antistatic compound has a molecular weight of ≥1000 and ≤5000 g / mol.
[0027] The antistatic compound may, for example, be a compound selected from the group consisting of: 2,2,6,6-tetramethyl-piperidine; 1,2,2,6,6-pentamethyl-piperidine; N,N'-bis(2,2,6,6-tetramethyl-piperidin-4-yl)hexamethylene-1,6-diamine; bis(2,2,6,6-tetramethyl-piperidin-4-yl)amine; N,N'-bis(2,2,6,6-tetramethyl-piperidin-4-yl)-N,N'-dicyclohexyl-2-hydroxypropylidene-1,3-diamine; 1-n-octyl-2,2,6,6-tetramethyl-piperidine; 1-benzyl-2,2,6,6-tetramethyl-piperidine; 2,6-di-tert-butyl-4-(1,2,2,6,6-pentamethyl-piperidin-4-ylmethyl)-phenol; dibutyl-(1,2 ,2,6,6-pentamethyl-piperidin-4-yl)-amine; N,N',N"-tributyl-N,N',N"-tri-(2,2,6,6-tetramethyl-piperidin-4-yl)-[1,3,5]triazine-2,4,6-triamine; 1-(but-3-enyl)-2,2,6,6-tetramethyl-piperidine; 2,2,6,6-tetramethyl-4-undec-10-enyl-piperidine; 1-(undec-10-enyl)-2,2,6,6-tetramethyl-piperidine; 4-(undec-10-enylamide)-1,2,2,6,6-pentamethylpiperidine; 4-((N-n-butyl)-undec-10-enylamide)-1,2,2,6,6-pentamethylpiperidine; 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-Benzyl-4-hydroxy-2,2,6,6-tetramethylpiperidine; 4-stearoyloxy-2,2,6,6-tetramethylpiperidine; 1-ethyl-4-salicyloyloxy-2,2,6,6-tetramethylpiperidine; bis(2,2,6,6-tetramethylpiperidin-4-yl)succinate; N,N'-bis(2,2,6,6-tetramethylpiperidin-4-yl)succinamide; hexane-1',6'-bis(4-carbamoyloxy-1-n-butyl-2,2,6,6-tetramethylpiperidine); dimethylbis(2,2,6,6-tetramethylpiperidin-4-oxy)silane; 2-[n-butyl(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-4,6-bis(diethylamino)-1,3,5-triazine ; 2,4,6-tris[ethyl(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-1,3,5-triazine; 2,4-bis[n-butyl(2,2,6,6-tetramethyl-4-piperidinyl)amino]-6-methyl-1,3,5-triazine; bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate; and N,N"'-1,2-ethanediylbis[N-[3-[[4,6-bis[butyl(1,2,2,6,6-pentamethyl-4-piperidinyl)amino]-1,3,5-triazine-2-yl]amino]propyl]-N',N"-dibutyl-N',N"-bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-1,3,5-triazine-2,4,6-diamine.
[0028] Preferably, the antistatic compound is an oligomeric or polymeric compound comprising a 2,2,6,6-tetramethylpiperidine moiety, for example selected from poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl]-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]-hexamethylene-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]; poly-methylpropyl-3-oxy-4-(2,2,6,6-tetramethyl-piperidinyl)siloxane; poly[(6-morpholine-s-triazine-2,4-diyl]-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]; -triazine-2,4-diyl)-(2,2,6,6-tetramethyl-4-piperidinyl)imino-hexamethylene-(2,2,6,6-tetramethyl-4-piperidinyl)imino]; poly[(6-cyclohexylamino-s-triazine-2,4-diyl]-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]-hexamethylene-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]; and poly[(2,2,6,6-tetramethyl-4-piperidinyl)imino)-propane-1,3-diyl].
[0029] In addition to its antistatic function due to the presence of amino functional groups, the antistatic compound can also prevent sheeting by adhering to the inner wall of the reactor and the inner surface of the feed line, the recirculation line and other exposed surfaces inside the polymerization reactor system, thereby forming a coating that prevents sheeting. In particular, such a coating effect occurs when an oligomeric or polymeric compound is used as an antistatic agent.
[0030] The co-catalyst promoter may, for example, be an alkylaluminum compound, preferably selected from trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum chloride, ethylaluminum dichloride, ethylaluminum sesquichloride and diethylaluminum ethoxide, more preferably selected from trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum and tri-n-octylaluminum, even more preferably the co-catalyst promoter is triisobutylaluminum.
[0031] The molar ratio of aluminum in the co-catalyst promoter to the moiety of formula I in the antistatic compound may be, for example, >0.5 and <3.0, preferably >0.75 and <2.5, more preferably >1.0 and <2.5, even more preferably >1.5 and <2.5.
[0032] In certain embodiments of the present invention, the cocatalyst and the antistatic agent can be provided to the polymerization in the form of a mixture. Such a mixture can be supplied in an amount of ≥0.1 and ≤10.0 wt %, preferably ≥0.2 and ≤5.0 wt %, more preferably ≥0.2 and ≤2.0 wt %, relative to the weight of the catalyst system.
[0033] In certain embodiments of the present invention, the co-catalyst aid and the antistatic agent can be provided to the polymerization in the form of a mixture. Such a mixture can be supplied in an amount of ≥0.1 and ≤10.0 wt %, preferably ≥0.2 and ≤5.0 wt %, more preferably ≥0.2 and ≤2.0 wt %, relative to the weight of the catalyst system.
[0034] In certain embodiments of the present invention, the cocatalyst and the antistatic agent can be provided to the catalyst system as a mixture during the preparation of the catalyst. Such a mixture can be supplied in an amount of ≥0.1 and ≤10.0 wt %, preferably ≥0.2 and ≤5.0 wt %, more preferably ≥0.2 and ≤2.0 wt %, relative to the weight of the catalyst system.
[0035] In certain embodiments of the present invention, the co-catalyst adjuvant and the antistatic agent can be provided to the catalyst system as a mixture during the preparation of the catalyst. Such a mixture can be supplied in an amount of ≥0.1 and ≤10.0 wt %, preferably ≥0.2 and ≤5.0 wt %, more preferably ≥0.2 and ≤2.0 wt % relative to the weight of the catalyst system.
[0036] In other embodiments, the mixture of cocatalyst and antistatic agent can be added to the polymerization reactor via injection by monomer feed line, comonomer feed line or recycle line. The mixture can be supplied as a solution, and the sight glass / glass electric valve with orifice feed arrangement at the position above the distribution plate of the reactor is used to measure to the reactor. Based on the static charge monitored by the electrostatic probe, the mixture can be supplied continuously or intermittently. The amount of the mixture added to the polymerization reaction can be, for example, in a weight meter relative to the polymer product of ≥1 and ≤1000ppm weight, preferably ≥1 and ≤5000ppm, more preferably ≥10 and ≤200ppm in the range.
[0037] In other embodiments, the mixture of cocatalyst adjuvant and antistatic agent can be added to the polymerization reactor via injection through monomer feed line, comonomer feed line or recycle line. The mixture can be supplied as a solution, and the reactor is metered using a window / glass electric valve with an orifice feed arrangement at a position above the distributor plate of the reactor. Based on the static charge monitored by an electrostatic probe, the mixture can be supplied continuously or intermittently. The amount of the mixture added to the polymerization reaction can be, for example, in a weight meter relative to the polymer product of ≥1 and ≤1000ppm weight, preferably ≥1 and ≤5000ppm, more preferably ≥10 and ≤200ppm.
[0038] In one embodiment of the present invention, the catalyst system, the aluminum-containing cocatalyst, the aluminum-containing cocatalyst adjuvant and the antistatic compound may be provided to the polymerization in the form of a catalyst, wherein the catalyst is prepared by contacting the catalyst system, the cocatalyst, the cocatalyst adjuvant and the antistatic compound.
[0039] In one embodiment, the present invention is also directed to a process comprising preparing a catalyst by contacting a catalyst system, a cocatalyst, a cocatalyst adjuvant, and an antistatic compound, and polymerizing a reaction composition comprising ethylene in the presence of the catalyst.
[0040] In an alternative embodiment, the antistatic agent may be premixed with the catalyst system prior to adding it to the reactor.
[0041] The reaction composition preferably comprises ethylene and optionally one or more comonomers selected from propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene and 1-octene; more preferably, the reaction composition comprises ethylene and optionally one or more comonomers selected from propylene, 1-butene, 1-hexene and 1-octene.
[0042] The cocatalyst is preferably selected from methylaluminoxane, borane or borate compounds, preferably selected from methylaluminoxane, perfluorophenylborane, triethylammonium tetrakis(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate, trimethylsilyl tetrakis(pentafluorophenyl)borate, 1-pentafluorophenyl-1,4-dihydroborabenzene, tributylammonium 1,4-bis(pentafluorophenyl)borabenzene and triphenylcarbonium 1-methylborabenzene, more preferably the cocatalyst is methylaluminoxane.
[0043] The catalyst system may, for example, be a single-site catalyst system, preferably a metallocene-type catalyst system; a Ziegler-Natta-type catalyst system; or a chromium-containing Phillips-type catalyst system.
[0044] Preferably, the catalyst system is a metallocene-type catalyst system, preferably comprising a compound selected from the group consisting of: [2,2'-bis(2-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(2-indenyl)biphenyl]hafnium dichloride; [2,2'-bis(1-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(1-indenyl)biphenyl]hafnium dichloride; [(2-(2-indenyl)-2'-cyclopentadienyl)biphenyl]zirconium dichloride; [(2-(2-indenyl)-2'-cyclopentadienyl)biphenyl]hafnium dichloride; [1,2-bis(2-indenyl)phenyl]zirconium dichloride; [1,2-bis(2-indenyl)phenyl]hafnium dichloride; [2,2'-bis(5-phenyl-2-indenyl)biphenyl]zirconium dichloride; [2, [2'-bis(5-phenyl-2-indenyl)biphenyl] hafnium dichloride; [2,2'-bis(4,7-dimethyl-2-indenyl)biphenyl] zirconium dichloride; [2,2'-bis(4,7-dimethyl-2-indenyl)biphenyl] hafnium dichloride; [2,2'-bis(4-fluoro-2-indenyl)biphenyl] zirconium dichloride; [2,2'-bis(4-fluoro-2-indenyl)biphenyl] [(1,2,3,3a,7a-η)-2-(1-methylethyl)-1H-inden-1-ylidene](dimethylsilyl)dichloro] (1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride [[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride [[(1,2,3,3a,7a-η)-2-methyl-4-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride [[(1,2,3,3a,7a-η)-2-methyl-4-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride [(1,2,3,3a,7a-η)-2-phenyl-3-methyl-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; [[(1,2,3,3a,7a-η)-2-phenyl-3-methyl-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; [[(1,2,3,3a,7a-η)-2-phenyl-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,3a,7a-η)-1H-inden-2-ylidene]]-zirconium dichloride;Zirconium dichloride [[(1,2,3,3a,7a-η)-2-(3,5-dimethylphenyl)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,3a,7a-η)-1,3-dimethyl-1H-inden-2-ylidene]]; [[(1,2,3,3a,7a-η)-2-(1-methylethyl)-1H-inden-1-ylidene](dimethylsilylene) dichloro[[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-hafnium; and dichloro[[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-hafnium. ;
[0045] The catalyst system can, for example, be a supported catalyst system, and preferably the support material can be selected from silica, alumina, magnesia, titania, zirconia, clay, zeolite, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polycarbonate, polyketone, polyvinyl alcohol, polymethyl methacrylate, cellulose and graphite, and more preferably the support material is silica.
[0046] Such silicon dioxide preferably has a large specific surface area, preferably 50 to 500 m 2 / g and high pore volume, preferably 0.5 to 2.0 cm 3 / g of fine particles. If the catalyst is to be used in a solution polymerization process, the average particle size of the silica may be, for example, 3 to 20 μm; or if the catalyst is to be used in a gas phase polymerization process, the average particle size of the silica may be, for example, 30 to 100 μm; or if the catalyst is to be used in a slurry polymerization process, the average particle size of the silica may be, for example, 5 to 80 μm.
[0047] Prior to fixing the metallocene precursor on the silica, the silica is typically treated at high temperature, such as at a temperature of 450°C to 700°C, in a fluidized bed reactor under nitrogen flow for several hours, such as 3 to 6 hours.
[0048] The molar ratio of the co-catalyst to the metallocene in the catalyst system can be, for example, ≥1.0 and ≤1000, preferably ≥50.0 and ≤300.0 when the co-catalyst is an organoaluminum compound; and can be, for example, ≥1.0 and ≤50.0, preferably ≥1.0 and ≤10.0 when the co-catalyst is a non-coordinating anionic compound.
[0049] Preferably, the catalyst system comprises ≥6.0 and ≤30.0 wt. %, preferably ≥7.0 and ≤17.0 wt. %, more preferably ≥10.0 and ≤16.0 wt. % Al, relative to the total weight of the catalyst system. Preferably, the catalyst system comprises ≥0.10 and ≤1.00 wt. %, preferably ≥0.15 and ≤0.50 wt. %, more preferably ≥0.15 and ≤0.30 wt. % Zr or Hf, relative to the total weight of the catalyst system.
[0050] The process can be carried out, for example, at a pressure of ≥10 and ≤80 MPa, preferably ≥20 and ≤60 MPa and at a temperature of ≥40 and ≤100°C, preferably ≥60 and ≤90°C, more preferably ≥60 and ≤85°C.
[0051] The process can be, for example, a slurry polymerization process, a solution polymerization process, a gas phase polymerization process, a bulk polymerization process or a combination thereof. Preferably, the process is a gas phase polymerization process. Particularly preferably, such a gas phase polymerization process is operated in a condensing mode or a super condensing mode.
[0052] The ethylene-based polymer that can be produced according to the process of the present invention can be, for example, a homopolymer or a copolymer. Such an ethylene-based copolymer can be a polymer comprising a structural portion derived from ethylene and a structural portion derived from a comonomer compound, the comonomer compound being selected from propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene and 1-octene, preferably selected from 1-butene, 1-hexene and 1-octene. Such a copolymer can, for example, contain ≥0.2 and ≤30.0 wt. %, preferably ≥1.0 and ≤25.0, more preferably ≥5.0 and ≤20.0 wt. % of a structural portion derived from a comonomer compound relative to the total weight of the ethylene-based polymer. Such ethylene-based copolymers may alternatively be terpolymers comprising moieties derived from ethylene, a first comonomer compound, and a second comonomer compound; the first comonomer compound being selected from propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, and 1-octene, preferably selected from 1-butene, 1-hexene, and 1-octene; the second comonomer compound being selected from propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, and 1-octene, preferably selected from 1-butene, 1-hexene, and 1-octene, wherein the first comonomer compound is different from the second comonomer compound. Such terpolymers may, for example, comprise ≥5.0 and ≤50.0 wt%, preferably ≥10.0 and ≤30.0, more preferably ≥10.0 and ≤25.0 wt% of moieties derived from the first and second comonomer compounds, relative to the total weight of the ethylene-based polymer.
[0053] The ethylene-based polymers that can be produced using the process according to the present invention can, for example, have a molecular weight of ≥0.850 and ≤0.975 g / cm 3 For example, an ethylene-based polymer may have a density of ≥0.850 and ≤0.905 g / cm 3 Ethylene-based elastomers (POE) or plastomers (POP) having a density of ≥0.906 and ≤0.925 g / cm 3 Linear low-density polyethylene (LLDPE) with a density of ≥0.926 and ≤0.940 g / cm 3 Linear medium density polyethylene (MDPE) with a density of ≥0.941 and ≤0.975 g / cm 3 The density of linear high density polyethylene (HDPE) can be measured according to ASTM D792 (2008).
[0054] The ethylene-based polymer may, for example, have a melt mass flow rate of ≥0.1 and ≤50.0 g / 10 min, preferably ≥0.5 and ≤30.0 g / 10 min, more preferably ≥1.0 and ≤10.0 g / 10 min, even more preferably ≥1.0 and ≤5.0 g / 10 min, measured at 190° C. and 2.16 kg load according to ISO 1133:2005.
[0055] In the context of the present invention, the terms antistatic agent and antistatic compound are interchangeable.
[0056] The invention will now be illustrated by the following non-limiting examples.
[0057] The method of the invention is now demonstrated by means of polymerization experiments as described below. In Table 1 the materials used in the polymerization experiments are shown.
[0058] Table 1
[0059]
[0060] All materials were handled in a nitrogen atmosphere using Schlenk techniques or a nitrogen-filled glove box. Nitrogen and isopentane were dried over an additional molecular sieve bed. All other solvents were first dried over molecular sieves and sodium / potassium amalgam. The catalyst was prepared in a silicone oil bath with stirring using a temperature controlled within 0.5°C. 944 and 2020 was dried at 80 °C under vacuum for 12 h.
[0061] Preparation of a mixture of a co-catalyst, an auxiliary agent and an antistatic agent
[0062] Using the materials and amounts of such materials shown in Table 2, a series of mixtures comprising TIBAL and an antistatic agent were prepared according to the following method.
[0063] In a glove box under nitrogen atmosphere, 15 ml of hexane was charged into a 50 ml vial. At room temperature, a certain amount of TIBAL was added to the vial, and then a given amount of the listed antistatic agent was slowly added. The obtained solution contained 1 M TIBAL.
[0064] The mixtures of Examples A15, A16 and A17 were prepared according to the methods of Examples A2, A5 and A10, respectively, but additionally the mixtures were subsequently heated at 70° C. for 4 hours in order to investigate the effect of temperature on the properties of the mixtures.
[0065] Table 2
[0066] Example TIBAL amount (g) Antistatic agent (AA) AA amount (g) Molar ratioTIBAL / AA Appearance of solution A1 3.93 - - 1:0 colorless A2 3.93 AA1 0.65 3:1 colorless A3 3.93 AA1 0.98 2:1 colorless A4 3.93 AA1 1.96 1:1 colorless A5 3.93 AA2 1.15 3:1 colorless A6 3.93 AA2 1.72 2:1 colorless A7 3.93 AA2 3.45 1:1 Light yellow A8 3.93 AA2 6.90 1:2 Light yellow A9 - AA2 6.90 0:1 Light yellow A10 3.93 AA3 1.88 3:1 colorless A11 3.93 AA3 2.82 2:1 colorless A12 3.93 AA3 5.65 1:1 Light yellow A13 3.93 AA3 11.30 1:2 Light yellow A14 - AA3 11.30 0:1 Light yellow A15 3.93 AA1 0.65 3:1 colorless A16 3.93 AA2 1.15 3:1 colorless A17 3.93 AA3 1.88 3:1 colorless
[0067] In Table 2, the molar ratio TIBAL / AA represents the molar ratio of TIBAL to the amino functional group(s) of the antistatic agent. According to their molecular structures, AA1, AA2 and AA3 contain 1 mole of amino functional group per 99 g, 174 g and 285 g, respectively.
[0068] Example A1 represents a co-catalyst solution without any antistatic agent and is provided for comparative purposes to demonstrate that the productivity of the catalyst is not affected by the presence of an antistatic agent.
[0069] Preparation of supported metallocene complexes
[0070] Catalyst B0
[0071] A 3-liter autoclave reactor equipped with a heating / cooling control unit and a mechanical stirring system was baked at 150°C (inlet oil) under a nitrogen stream for 2 hours and then cooled to 30°C. 200g of GraceSilica 955 pre-dehydrated at 600°C for 10 hours was loaded, followed by the addition of 800ml of toluene. 3.32g of [2,2'-bis(2-indenyl)biphenyl]zirconium dichloride was activated by mixing with 1203.6ml of a 10 wt% MAO toluene solution at 50°C for 30min to obtain an activated metallocene. The activated metallocene was transferred to an autoclave reactor under stirring. An antistatic agent modifier was prepared by reacting 0.31g of cyclohexylamine and 0.62g of triisobutylaluminum in 200ml toluene added to the autoclave, and the reaction mixture was stirred at 95°C for 5 hours. After drying at 75°C under vacuum (13.5kPa), the finished catalyst was isolated as a light yellow free-flowing powder. The catalyst contained 0.18 wt. % Zr and 16.0 wt. % Al. This resulted in a molar ratio of Al / Zr of about 300.
[0072] Catalyst B1-B13
[0073] In a glove box under a nitrogen atmosphere, 2.5g of Grace Silica 955 carrier pre-dehydrated at 600°C for 4 hours was loaded into a 100ml double-necked Schlenk flask, and 15ml of toluene was then added. A suspension was obtained after shaking. 0.042g of metallocene was activated by mixing 10 weight % solution of 15.2ml of co-catalyst in toluene in a 25ml vial at room temperature for 10min in a glove box also under a nitrogen atmosphere to obtain an activated metallocene mixture. The activated metallocene mixture was transferred to the suspension. In a glove box, a given amount of co-catalyst and antistatic agent as shown in Table 3 below was mixed in another 25ml vial in 10ml toluene at room temperature for 10min and then transferred to the suspension. The final mixture was heated to 95°C and kept at this temperature for 5 hours. Subsequently, the product was dried under vacuum at 75°C to obtain a supported catalyst, which was separated into a free-flowing powder. The supported catalysts each contained 0.18 wt% Zr and 16.0 wt% Al, which translates to a molar ratio of Al to Zr of about 300. The molar ratio of TIBAL to the amino functional group(s) of the antistatic agent in each of Examples B2-B13 was 1:1.
[0074] Table 3
[0075] Example TIBAL amount (g) Antistatic agent (AA) AA amount (g) Molar ratio Zr / AA B1 - - - 1:0 B2 0.0075 AA1 0.0038 1:0.5 B3 0.015 AA1 0.0076 1:1 B4 0.0375 AA1 0.019 1:2.5 B5 0.075 AA1 0.038 1:5 B6 0.0079 AA2 0.0071 1:0.5 B7 0.0155 AA2 0.0136 1:1 B8 0.0388 AA2 0.0342 1:2.5 B9 0.0776 AA2 0.0684 1:5 B10 0.0075 AA3 0.0108 1:0.5 B11 0.015 AA3 0.022 1:1 B12 0.0375 AA3 0.055 1:2.5 B13 0.075 AA3 0.11 1:5
[0076] In Table 3, the molar ratio Zr / AA represents the molar ratio of zirconium in the metallocene to the amino functional group(s) of the antistatic agent.
[0077] Aggregation experiments
[0078] Effect of using a mixture of a co-catalyst and an antistatic agent
[0079] In order to determine the effect of using a mixture of a co-catalyst promoter and an antistatic agent as prepared in Examples A1-A17, a set of polymerization experiments were carried out using Catalyst B0. The polymerization experiments were carried out by slurry polymerization.
[0080] A 1.6 1 stainless steel reactor vessel equipped with a helical stirrer and a heating / cooling control unit was heated to 110°C for 2 hours at a nitrogen flow rate of 100 g / h. Afterwards, the reactor was purged with nitrogen pressure and then with ethylene. This purge cycle was repeated three times.
[0081] The reactor is then cooled to 88°C under an ethylene pressure of 10 bar. After exhaust, 100 ml of hexane is added by a co-catalyst injection pump, followed by 4 ml of a co-catalyst adjuvant / antistatic mixture. The specific mixture for each polymerization experiment is shown in Table 4 below. Nitrogen is introduced to maintain a nitrogen pressure of 7 bar. Ethylene is then introduced into the reactor under the control of mass flow parameters to maintain the ethylene pressure in the reactor of 10 bar. After reaching a stable temperature and pressure level, 25 mg of catalyst B0 is injected by a catalyst injection pump, thus starting the reaction. After 1 hour, the ethylene supply is stopped and the reactor is cooled to 40°C. The reactor is opened after exhaust. The polyethylene product formed in the reactor is collected in a sample tray and dried at ambient temperature under atmospheric pressure. The results of the polymerization are shown in Table 4.
[0082] Table 4
[0083] Example Co-catalyst / AA mixture PE output (g) PE productivity (g PE / g cat) C1 A1 58.0 2320 C2 A2 28.6 1143 C3 A3 6.8 270 C4 A4 0 0 C5 A5 58.2 2329 C6 A6 27.3 2290 C7 A7 55.1 2203 C8 A8 30.4 1216 C9 A9 1.5 60 C10 A10 50.2 2008 C11 A11 49.6 1984 C12 A12 38.5 1540 C13 A13 30.9 1234 C14 A14 1.5 60 C15 A15 43.8 1750 C16 A16 57.1 2282 C17 A17 46.4 1857
[0084] It can be seen that in Examples C2-C4 using antistatic agent AA1, the catalyst productivity significantly decreased with the increase in the amount of antistatic agent. The same trend can be observed in Examples C10-C14 where antistatic agent AA3 is used. However, in Examples C5-C9 where antistatic agent AA2 is used, the catalyst does not substantially change with the increase in the amount of antistatic agent, particularly for the examples where the ratio of TIBAL to antistatic agent is in the range of 3:1 to 1:1.
[0085] When considering the effect of the heat treatment in Examples A15-A17 on the mixture of A2, A5 and A10, it can be observed that in Example C15, the catalyst productivity is increased compared to C2, while in Examples C16 (compared to C5) and C17 (compared to C10), the catalyst productivity is quite comparable.
[0086] In the examples where antistatic agents were used, no sheeting was observed.
[0087] Effect of using antistatic agents added during catalyst synthesis
[0088] The effect of using various mixtures of cocatalyst promoters and antistatic agents as part of the catalytic system prepared as in Examples B1-B13 in ethylene polymerization was investigated by carrying out a number of polymerization experiments in the gas phase.
[0089] A 1.6 1 stainless steel reactor vessel equipped with a helical stirrer and a heating / cooling control unit was heated to 110°C for 2 hours at a nitrogen flow rate of 100 g / h. Afterwards, the reactor was purged with nitrogen pressure and then with ethylene. This purge cycle was repeated three times.
[0090] The reactor was then cooled to 88°C under an ethylene pressure of 10 bar. After venting, 4 ml of AXION PA 4276 available from Lanxess was added by a cocatalyst injection pump. Nitrogen was introduced to maintain a nitrogen pressure of 8 bar. Ethylene was then introduced into the reactor under the control of mass flow parameters to maintain the ethylene pressure in the reactor of 10 bar. After reaching a stable temperature and pressure level, 40 mg of catalyst was injected by a catalyst injection pump, and the reaction was started. The catalyst used for each embodiment is shown in Table 5 below. After 1 hour, the ethylene supply was stopped and the reactor was cooled to 40°C. The reactor was opened after venting. The polyethylene product formed in the reactor was collected to a sample tray and dried at ambient temperature under atmospheric pressure. The results of the polymerization are shown in Table 5.
[0091] Table 5
[0092] Example catalyst PE output (g) PE productivity (g PE / g cat) D1 B1 53.6 1341 D2 B2 52.6 1315 D3 B3 50.6 1266 D4 B4 50.4 1259 D5 B5 47.2 1179 D6 B6 52.8 1320 D7 B7 50.2 1256 D8 B8 48.4 1210 D9 B9 48.2 1206 D10 B10 55.6 1389 D11 B11 51.4 1284 D12 B12 49.5 1237 D13 B13 51.2 1281
[0093] It can be observed that with increasing amount of mixture of TIBAL and antistatic agent, catalyst activity gradually decreases, but not significantly. It has been observed that for all antistatic agents, the presence of mixture of TIBAL and antistatic agent in catalyst can be used as antistatic agent and scavenger without substantially affecting catalyst productivity.
[0094] No sheeting was observed in the examples where antistatic agents were used.
Claims
1. A process for producing an ethylene-based polymer, wherein the process is carried out by polymerizing a reaction composition comprising ethylene in the presence of a catalyst system, an aluminum-containing cocatalyst, an aluminum-containing cocatalyst adjuvant, and an antistatic compound comprising one or more moieties according to formula I: in: ● R1 is H or an aliphatic moiety containing 1 to 4 carbon atoms, preferably H or CH3, more preferably H; ● R4 and R5 are moieties containing 1 to 10 carbon atoms, preferably aliphatic or aromatic moieties containing 1 to 10 carbon atoms, more preferably -CH2CH3 or CH3; ● R3 and R6 are H or a moiety containing 1 to 10 carbon atoms, preferably an aliphatic or aromatic moiety containing 1 to 10 carbon atoms, more preferably -CH2CH3 or CH3; ● R2 is H; a moiety comprising 1 to 10 carbon atoms, preferably an amine, aliphatic or aromatic moiety comprising 1 to 10 carbon atoms; or R2 forms a linker to a polymer structure, wherein the compound of formula I forms a functional moiety attached to the polymer chain; Preferably, the antistatic compound has a molecular weight of ≥1000 and ≤5000 g / mol.
2. The process according to claim 1, wherein the process is a gas phase polymerization process.
3. The method according to any one of claims 1-2, wherein R1 is H.
4. The method according to any one of claims 1 to 3, wherein the structural moiety of formula I is a 2,2,6,6-tetramethylpiperidine structural moiety.
5. The method according to any one of claims 1 to 4, wherein the moiety of formula I forms part of a polymeric structure having a polymer repeating unit according to formula II: in: ● R1 is H or an aliphatic moiety containing 1 to 4 carbon atoms, preferably H or CH3, more preferably H; ● R7 is an alkyl moiety, preferably an alkyl moiety containing 4 to 10 carbon atoms, more preferably -(CH2) x - a moiety wherein x is 4 to 10, preferably x is 6; and ● Each of R8 and R9 is H; a moiety containing 1 to 10 carbon atoms, preferably an aliphatic or aromatic moiety containing 1 to 10 carbon atoms, more preferably n-butyl, tert-butyl or tert-octyl; 2,2,6,6-tetramethyl-4-piperidinyl; or 4,6-bis(di-n-butylamino)-1,3,5-triazin-2-yl; And preferably, n≥1 and≤10.
6. The method according to claim 5, wherein: ● R8 is H and R9 is tert-butyl or tert-octyl; or ● R8 is n-butyl and R9 is 2,2,6,6-tetramethyl-4-piperidinyl.
7. The method according to any one of claims 1 to 6, wherein the co-catalyst promoter is an alkyl aluminum compound, preferably selected from trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum chloride, ethylaluminum dichloride, ethylaluminum sesquichloride and diethylaluminum ethoxide, more preferably selected from trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, tri-n-hexylaluminum and tri-n-octylaluminum, even more preferably the co-catalyst promoter is triisobutyl aluminum.
8. according to the method described in any one of claims 1-7, the molar ratio of the aluminum in the wherein said co-catalyst adjuvant to the structural part of formula I in the said antistatic compound is>0.5 and<3.0, preferably>0.75 and<2.5, more preferably>1.0 and<2.5, even more preferably>1.5 and<2.
5.
9. The process according to any one of claims 1 to 8, wherein the co-catalyst aid and the antistatic agent are provided to the polymerization in the form of a mixture.
10. The method according to any one of claims 1 to 8, wherein the catalyst system, the aluminum-containing co-catalyst, the aluminum-containing co-catalyst adjuvant and the antistatic compound are provided to the polymerization in the form of a catalyst, wherein the catalyst is prepared by contacting the catalyst system, the co-catalyst, the co-catalyst adjuvant and the antistatic compound.
11. The process according to any one of claims 1 to 10, wherein the reaction composition comprises ethylene and optionally one or more comonomers selected from the group consisting of propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene and 1-octene; preferably wherein the reaction composition comprises ethylene and optionally one or more comonomers selected from the group consisting of propylene, 1-butene, 1-hexene and 1-octene.
12. The method according to any one of claims 1 to 11, wherein the cocatalyst is selected from methylaluminoxane, borane or borate compounds, preferably selected from methylaluminoxane, perfluorophenylborane, triethylammonium tetrakis(pentafluorophenyl)borate, triphenylcarbonium tetrakis(pentafluorophenyl)borate, trimethylsilyl tetrakis(pentafluorophenyl)borate, 1-pentafluorophenyl-1,4-dihydroborabenzene, tributylammonium 1,4-bis(pentafluorophenyl)borabenzene and triphenylcarbonium 1-methylborabenzene, more preferably the cocatalyst is methylaluminoxane.
13. The method according to any one of claims 1 to 12, wherein: ● The catalyst system is a single-site catalyst system, preferably a metallocene catalyst system; a Ziegler-Natta catalyst system; or a chromium-containing Phillips catalyst system; and • Preferably, the process is carried out at a pressure of ≥10 and ≤80 MPa and at a temperature of ≥40 and ≤100°C.
14. The process according to any one of claims 1 to 13, wherein the catalyst system is a metallocene-type catalyst system, preferably comprising a compound selected from the group consisting of: [2,2'-bis(2-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(2-indenyl)biphenyl]hafnium dichloride; [2,2'-bis(1-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(1-indenyl)biphenyl]hafnium dichloride; [(2-(2-indenyl)-2'-cyclopentadienyl)biphenyl]zirconium dichloride; [(2-(2-indenyl)-2'-cyclopentadienyl)biphenyl]hafnium dichloride; [1,2-bis(2-indenyl)phenyl]zirconium dichloride; [1,2-bis(2-indenyl)phenyl]hafnium dichloride; [2,2'-bis(5-phenyl [2,2'-Bis(5-phenyl-2-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(4,7-dimethyl-2-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(4,7-dimethyl-2-indenyl)biphenyl]hafnium dichloride; [2,2'-bis(4,7-dimethyl-2-indenyl)biphenyl]zirconium dichloride; [2,2'-bis(4-fluoro-2-indenyl)biphenyl]zirconium dichloride; [2,2'-Bis(4-fluoro-2-indenyl)biphenyl]hafnium dichloride; [2,2'-Bis(5,7-di-tert-butyl-2-indenyl)biphenyl]zirconium dichloride; [2,2'-Bis(5,7-di-tert-butyl-2-indenyl)biphenyl]hafnium dichloride; [[(1,2,3,3a,7a-η)-2-(1-methylethyl)-1H-inden-1-ylidene]dichloride ](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; [[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; [[(1,2,3,3a,7a-η)-2-methyl-4-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; ,3a,7a-η)-3-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride; [[(1,2,3,3a,7a-η)-2-phenyl-3-methyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-zirconium dichloride Zirconium dichloride [[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,3a,7a-η)-1H-indene-2-ylidene]];Zirconium dichloride [[(1,2,3,3a,7a-η)-2-(3,5-dimethylphenyl)-1H-inden-1-ylidene](dimethylsilylene)[(1,2,3,3a,7a-η)-1,3-dimethyl-1H-inden-2-ylidene]]; [[(1,2,3,3a,7a-η)-2-(1-methylethyl)-1H-inden-1-ylidene](dimethylsilylene) dichloro[[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-hafnium; and dichloro[[(1,2,3,3a,7a-η)-2-phenyl-1H-indene-1-ylidene](dimethylsilylene)[(1,2,3,4,5-η)-2,3,4,5-tetramethyl-2,4-cyclopentadien-1-ylidene]]-hafnium. ; 15. The method according to any one of claims 1 to 14, wherein the catalyst system is a supported catalyst system, preferably wherein the support material is selected from silica, alumina, magnesia, titania, zirconia, clay, zeolite, polystyrene, polyethylene, polypropylene, polyvinyl chloride, polycarbonate, polyketone, polyvinyl alcohol, polymethyl methacrylate, cellulose and graphite, more preferably wherein the support material is silica.